Results of bent crystal channeling and collimation at the Relativistic Heavy Ion Collider - R. P. Fliller, III; A. Drees; D. Gassner; L. Hammons; G. McIntyre; S. Peggs; D. Trbojevic; V. Biryukov; Y. Chesnokov; V. Terekhov (Physical Review Special Topics. Accelerators and Beams, 2006)
Bent crystal channeling has been observed with protons and fully stripped gold ions in the Relativistic Heavy Ion Collider (RHIC). Prior to 2003, a bent crystal was installed in one ring of RHIC as the first stage of a two stage collimation system. The observed channeling efficiency was approximately 25%, less than half of original predictions. We show that this is due to a difference between the model and real Twiss parameters at the crystal location and our improved understanding of the beam halo. Collimation using the crystal was unsuccessful and raised background at the STAR detector by as much as a factor of 2 because of the low channeling efficiency. We give a report of our channeling studies in RHIC and describe our experience using the bent crystal as a collimator. The results are discussed and compared to simulations and theoretical predictions.